Multimedia Learning and UDL in UK Higher Education - C.A. Henshaw (Journal of Advanced Research in Education, 2025)
The integration of multimedia learning and Universal Design for Learning (UDL) in UK higher education has significantly enhanced student engagement, accessibility, and learning outcomes in asynchronous digital environments. Video lectures, interactive simulations, and AI-driven adaptive learning have improved knowledge retention and participation, yet challenges such as faculty preparedness, technological infrastructure, and accessibility disparities persist. This study examines the role of interactive content, gamification, and virtual reality (VR) in promoting active learning while addressing barriers related to the digital divide, institutional policies, and faculty training. Research indicates that students using adaptive learning technologies achieve higher retention and completion rates, while gamified learning environments foster greater motivation and participation. However, equitable access to digital resources and ethical AI governance remain critical concerns. Future strategies should focus on AI-driven personalization, immersive learning experiences, and expanded faculty development initiatives to ensure scalable and inclusive digital education. By leveraging emerging technologies, data-driven learning analytics, and open educational resources (OERs), UK universities can create more effective, accessible, and engaging learning experiences for diverse student populations.